Factors affecting air surface temperature variations in the Philippines - Lequiron, John Christian B.; Bagtasa, Gerry (Quezon City Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliman, 2016)
Changes in air surface temperature plays an important role in the Philippine's economy, industry, health, and food production. While increasing global mean temperature in the recent several decades has prompted a number of climate change and variability studies in the Philippines, most studies still focus on rainfall and tropical cyclones. This study aims to investigate the trend and variability of observed air surface temperature and determine its major influencing factor/s in the Philippines. The influence of ENSO teleconnection on temperature,wind pattern, cloud cover, and outgoing longwave radiation on different ENSO phases had significant effects on regional temperature variability. Particularly, an anomalous anticyclonic (cyclonic) flow east of the Philippines during the peak and decay phase of El Niño (La Niña) events leads to the advection of warm southeasterly (cold northeasterly) air mass over the country. Finally, an assessment of gridded temperature datasets were done to look at the viability of using three high-resolution datasets in future climate analysis and model calibration and verification. Several error statistics (i.e. Pearson correlation, Bias, MAE, and RMSE) were used for this validation. Results show that gridded temperature datasets generally follows the observed surface temperature change and anomalies. In addition, t is more representative of regional temperature rather than a substitute to station-observed air temperature.
Thesis (M.S. Meteorology)--University of the Philippines Diliman
Keywords: Climatic changes -- Philippines; Earth temperature -- Philippines